2009
DOI: 10.1021/bc8004599
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Circular Structures of i-Motif Tagged with Fluoresceins

Abstract: Synthesis of a fluorescein-tagged circular structure of i-motif was accomplished during our investigations. The backbone circularity of this molecular probe and the presence of the fluorescent moiety within its structure were also confirmed through exonuclease hydrolysis and fluorescence spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is accomplished by covalent bonding to one of the bases at the loops not involved in the i-motif core. 134 It was shown that this cyclic oligonucleotide resists the hydrolysis by exonucleases and the uorescent moiety is indeed present in the ligation product.…”
Section: Effects Of Chemical Modifications On the Stabilitymentioning
confidence: 99%
“…This is accomplished by covalent bonding to one of the bases at the loops not involved in the i-motif core. 134 It was shown that this cyclic oligonucleotide resists the hydrolysis by exonucleases and the uorescent moiety is indeed present in the ligation product.…”
Section: Effects Of Chemical Modifications On the Stabilitymentioning
confidence: 99%
“…179,180,568 Various fluorescein derivatives have been used, including a novel fluorescein phosphoramidite that has been described, 569 and a novel dC-modified derivative 139 as well as some modifications that are formed during oligonucleotide synthesis with the fluorescein HEX. 570 Other derivatives have been used to investigate DNA hybridisation under microwave conditions, 571 to monitor i-motif structures, 572 to measure endogenous RNA in living cells, 573 and in a new method for SNP typing. 574 Other fluorophores include the fluorescent guanine analogues 3MI or 6MI, 575 Cy-dyes to monitor antisense targeting in vivo, 576 the naturally fluorescent 8-aza-dG in hybridisation studies, 256 SYBR green to monitor silver ions in oligonucleotide structures, 577 a chemiluminescent analogue derived from acridine 578 and a ruthenium complex as part of an aptamer probe.…”
Section: Fluorescencementioning
confidence: 99%